Pengendalian Penyakit Busuk Pangkal Batang Lada dengan Ekstrak Pinang, Gambir, Sirih, dan Kapur Sirih - Dedek Kusvianti; Widodo Widodo; Djoko Prijono (Jurnal Fitopatologi Indonesia, 2014)
Pepper is an important commodity in Indonesia due to its export value. Infection of Phytophthora capsici causing stem rot disease is very critical for the production of pepper plants. Research was conducted to evaluate the efficiency of extracts of areca, gambir, betle, and lime paste for controlling stem rot disease. In vitro and in vivo experiments was designed to evaluate 2 factors, i.e. type and concentration of extracts. In vitro experiment was conducted by growing 4 day old and 5 mm in diameter of P. capsici isolate on V8 media containing the extracts tested. In vivo experiment was done by dipping pepper leaves on the extracts, followed by dropping zoospores of P. capsici on underneath of leaf surface. Mixture of 4 extracts (areca + gambir + betel + lime paste) of 0.005% and 0.01%; and areca extract of 0.04% was able to inhibit the growth of P. capsici colonies effectively in vitro. Similarly, mixture of 4 extracts of 0.01% effectively suppressed disease severity in vivo with equal effect with those of propineb fungicide of 0.2%.